PERANCANGAN GATE DRIVER MOSFET SiC DENGAN TEGANGAN PENGEMUDIAN NEGATIF UNTUK MEREDAM CROSSTALK - Putri, Intan Anggraeni Maryanda; Djuriatno, Waru; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
The rapid development of SiC MOSFET technology is due to its advantages over Si MOSFETs. In half-bridge configurations, SiC MOSFETs can cause EMI, ringing, and crosstalk from fast switching, requiring gate drivers to mitigate these issues. Conventional gate drivers (CGD) have limitations. This study assesses the negative voltage transistor-based assist gate driver (NVTAGD) in a half-bridge topology for its effectiveness in reducing crosstalk. NVTAGD reduces voltage overshoot by 21.02 dB and suppresses positive and negative crosstalk by 9.59 dB and 12.19 dB, respectively. Results show no shoot-through and no need for anadditional negative power supply. Although NVTAGD has a higher rise time, it enhances MOSFET reliability by effectively anaging crosstalk without extra control signals. Index Terms— MOSFET SiC, active gate driver, crosstalk, shoot-through, half bridge configuration